Severe teratozoospermia and its influence on pronuclear morphology, embryonic cleavage and compaction - Russell Helena; AbdelHafez Faten; Berger Dara S; Goldfarb James; Desai Nina (Reproductive Biology and Endocrinology, 2011)
Abstract Background Fertilization, cell division and embryo development depend on genomic contributions from male and female gametes. We hypothesize that teratozoospermic sperm influences early embryo development and embryo compaction. Methods We conducted a retrospective analysis of embryos derived from intracytoplasmic sperm injection (ICSI) cycles. Two hundred thirty-five consecutive ICSI cycles were included in the study; all treatment was provided at the Cleveland Clinic Fertility Center. Patient cycles were divided by sperm morphology based on Kruger's strict criteria: Group A, embryos where teratozoospermic sperm (0-2% normal) were used for ICSI and Group B, embryos where dysmorphic sperm (5-13% normal) were used for ICSI. All cycles analyzed were of patients doing day 3 embryo transfers. Outcome measures assessed included pronuclear (PN) pattern, syngamy, early cleavage, cell number, rate of compaction and blastulation of embryos left in culture and not transferred on day 3. Results A total of 1762 embryos were analyzed. PN patterns were similar in Group A and Group B embryos. No differences were noted in syngamy, cleavage, cell number or blastulation rate. Studying the development of embryos in culture after day 3 transfer revealed a difference in the timeline for compaction. By day 4, 25% of Group A embryos had compacted compared to 36% in Group B (P = 0.0007). There was no difference found between Group A and Group B embryos in regards to blastulation. Conclusions We did not find an association between sperm morphology and clinical outcomes. The impact of teratozoospermia may be masked in ICSI cycles where fertilization, implantation rate and clinical pregnancy rate are the primary outcome measures. However, by examining the timeline of development, we were better able to discern a potential paternal effect at critical transition points from fertilization through activation.